Aligning local governance with SDGs: a study of local government systems in Pakistan - Cheema, Abdur Rehman; Ahmad, I.; Mehmood, A. (Informa UK Limited, 2024)
This study examines the experiences of local government councilors between 2013–2020 in four provinces of Pakistan. The study addresses three key questions: Firstly, it investigates the differences and commonalities in the local government structures across provinces and explores the potential for synchronization to enhance the implementation of Sustainable Development Goals (SDGs) at the local level. Secondly, it examines the main challenges local councilors face in effectively delivering basic services, including water, sanitation, health, education, waste management, and transport, within both rural and urban contexts. Lastly, the study analyses the necessary changes or reforms at the provincial level within the existing local government system in rural and urban areas to ensure the delivery of basic services in alignment with SDGs. The findings reveal that a powerful bureaucracy and political influence at the intermediate to upper levels of the government hierarchy exert significant control over administrative, fiscal, and political.